Bridging Past And Future: Embedding Cultural Heritage In Sustainable Architecture Education Through Student Engagement (International Journal of Environmental Sciences, 2025)
This study employs a quantitative approach to investigate architecture students' perspectives on cultural heritage, highlighting its significance as a crucial component of cultural sustainability. It examines how students, as future architects, contribute to preserving and enhancing the built environment while incorporating cultural values into their designs. The research assesses students' responses based on three main themes: Cultural Heritage for Society, Awareness of Cultural Heritage, and the Transfer of Cultural Heritage. Early findings suggest that although students recognize the importance of cultural heritage in their initial education, a gap emerges as they progress to higher levels. The study highlights key factors shaping students' perceptions, underscoring the need for an educational framework that integrates cultural heritage into the architecture curriculum. By addressing these issues, this research proposes an academic framework that aims better to integrate cultural heritage into the field of architectural education. This effort aims to develop a new generation of architects who value and understand the importance of cultural sustainability, making cultural heritage a central part of their designs and a fundamental principle to preserve cultural, regional, and local identities in the built environment. Recognizing cultural heritage as a vital component ensures that relevant cultural aspects are considered in any specific context.